Reliability of the telephone-administered International Physical Activity Questionnaire in an Italian pilot sample (Epidemiology, Biostatistics, and Public Health, 2022)
Background: the International Physical Activity Questionnaire (IPAQ) is an instrument for crossnational monitoring of physical activity and inactivity. The aim of the study was the reliability evaluation of the Italian telephone-administered IPAQ version in Rome.Methods: the IPAQ short form (IPAQ-SF), consisting of 7 items, was administered. The responses, used to compute Metabolic Equivalent Task (MET in minutes per week), were processed to analyze the internal consistency. Standardized Cronbach’s alpha was used for reliability estimation.Results: a total of 133 adults (51 males and 82 females) participated in the study, with a mean age of 51 years (SD=19). The mean MET was 4 130, corresponding to good physical activity levels. The standardized Cronbach’s alpha on 6 items, concerning time spent on vigorous and moderate activity and walking, was 0.614.Conclusions: according to the findings from other countries, the Italian IPAQ-SF has acceptable measurement properties, as good as other established self-reports. The IPAQ-SF has a questionable reliability as previously reported, but the results of the present pilot study are promising and suggest that these instruments can be used to compare population estimates of physical activity.